2004
DOI: 10.1002/mc.20058
|View full text |Cite
|
Sign up to set email alerts
|

Mammary ECM composition and function are altered by reproductive state

Abstract: To address whether reproductive state alters mammary gland extracellular matrix (ECM) composition and function, ECM was isolated from nulliparous, pregnant, lactating, involuting, and regressed rat mammary glands. The ECM composition of fibronectin, tenascin, laminin, clusterin, and MMPs was found to vary dramatically with reproductive state. In 3-dimensional (3-D) culture, we identified novel effects of these endogenous mammary matrices on mammary epithelial cells. Specifically we found that (1) matrix isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
150
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(162 citation statements)
references
References 60 publications
12
150
0
Order By: Relevance
“…52 The number of CD68-positive cells was evaluated in the rat at day 6 postweaning (involution day 6), which corresponds to the peak of tissue remodeling during mammary involution. 21,49 Stromal associated CD68 levels were sixfold higher at involution day 6 compared with mammary glands from age-matched nulliparous rats ( Figure 1A). Similarly, the number of CSF-1R-positive cells was increased eightfold on involution day 6 when compared with nulliparous controls ( Figure 1B).…”
Section: Macrophage Influx Into Involuting Rodent Mammary Glandmentioning
confidence: 97%
See 1 more Smart Citation
“…52 The number of CD68-positive cells was evaluated in the rat at day 6 postweaning (involution day 6), which corresponds to the peak of tissue remodeling during mammary involution. 21,49 Stromal associated CD68 levels were sixfold higher at involution day 6 compared with mammary glands from age-matched nulliparous rats ( Figure 1A). Similarly, the number of CSF-1R-positive cells was increased eightfold on involution day 6 when compared with nulliparous controls ( Figure 1B).…”
Section: Macrophage Influx Into Involuting Rodent Mammary Glandmentioning
confidence: 97%
“…49 Briefly, 3% polyacrylamide (29:1) gels were prepared using 9.2 mmol/L calcium lactate, pH 6.8; 0.1% TEMED; and 0.07% ammonium persulfate only and pre-run for 1.5 hours at 100 volts with 50 mmol/L Tris, pH 6.6 lactic acid buffer in the cathode region and 0.1 mol/L lactic acid, pH 2.5 in the anode region with reversed electrodes. Mammary ECM samples from involution day 4 to 6 rats were prepared in 0.1 mol/L lactic acid, pH 2.5, and run for 2.5 hours at 70 volts with reversed electrodes.…”
Section: Collagen Western Blot Analysismentioning
confidence: 99%
“…Direct contact between stroma and non-malignant epithelia is not observed except during involution [50]. Breast cancers arising during pregnancy and involution tend to be highly aggressive and metastatic [51], suggesting that the collagen-1 rich stromal ECM, along with inflammatory environment observed in lactation and involution, could be pro-tumorigenic [52].…”
Section: Stromamentioning
confidence: 99%
“…Furthermore, nonmalignant epithelial cells exposed to increased density of stromallike collagen I and associated increases in ECM biomechanics undergo transition between formation of normal structures and loss of cell structure and increased growth [35]. The microarchitecture of the fibrilar collagen network (typically collagen I) in the stroma is believed to play a major role in specifying both risk of BC and the stiffness of the stromal ECM [37,50,54,55], suggesting that stiff stroma could encourage tumor initiation or progression. Depending on species, age and testing method, breast interstitial ECM has been measured to have a modulus of 167731 Pa [35], 0.4 kPa [37] and 1.13 70.78 kPa [55], and the risk of developing BC has been linked to increases in total breast stiffness both clinically [54].…”
Section: Stromamentioning
confidence: 99%
“…In addition, it is important to examine whether the stroma of parous animals supports proliferation of mammary epithelial cells in a quantitatively different manner than the stroma of AMVs. It has been demonstrated that the reproductive state does persistently alter mammary stroma extracellular matrix composition and function (Schedin et al 2004). …”
Section: Altered Hormonal Milieumentioning
confidence: 99%